Causality assessment of serious and severe adverse events following immunization in India: a 4-year practical experience. (3rd June 2018) - Singh, Awnish K.; Wagner, Abram L.; Joshi, Jyoti; Carlson, Bradley F.; Aneja, Satinder; Boulton, Matthew L.
ABSTRACT: Background : India has implemented the World Health Organization's revised Causality Assessment Protocol for adverse events following immunization (AEFI). We describe the number and types of serious/severe AEFIs, including deaths. Research design and methods : Analysis of causality classification of reported serious/severe AEFIs from 1 January 2012 to 7 January 2016 was done. Classification includes (A) consistent with causal association to immunization; (B) indeterminate; (C) coincidental association; or (D) unclassifiable. We present descriptive statistics across each category. Results : Analysis of causality assessment completed for 1037 reports of serious AEFIs: 499 (48%) were causally associated, 84 (8%) were indeterminate, 323 (31%) were coincidental, and 131 (13%) were unclassifiable. Of the 499 reports in the A category, the events were causally linked to vaccine product for 189 (18%), to immunization error for 135 (13%), and to immunization anxiety for 175 (17%). Among 279 reported deaths, more than half (55%; n  = 153) were coincidental events and 37% were unclassifiable. Conclusions : Causality assessment of AEFI cases is an important component of vaccination programs and post-marketing surveillance of vaccines. Field reporting and investigation of AEFIs can be improved for many severe or serious reports, most of which are not causally linked to the vaccination program.